The silver door / 2. - Rodda, Emily (Three doors trilogy, 2013)
Rye has defeated the sorcerer Olt, freed the island of Dorne, and rescued one of his brothers, but when he returns to the city of Weld with his three companions, he finds that very little has changed--the skimmer monsters still attack at night and the Warden is behaving very strangely.